Reducing Waste in Corrugated Box Packaging Before Printing: A Case Study of a Packaging Manufacturer - ตรีวิจิตร วรเทพ; พลเจริญ เถลิง; ศรีอาจ บรรเทิง; นามวงษา สมจัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The production process of corrugated paper often causes waste before entering the production process, resulting in waste and costs for the company. The objectives of this research are to 1) reduce waste of corrugated paper before entering the production process to no more than 3 percent and 2) establish correct work standards. Data collection of corrugated paper printing units before entering the production process shows that the most common waste is broken paper, followed by bent paper and adhesive paper that is not full of the corrugation, respectively. Therefore, the researcher analyzed the cause of the problem using a fishbone diagram and the principle of Why Why to solve the problem of establishing work standards and training employees. The research results showed that before the improvement, from May to July 2024, with an average production order of 162,124 sheets over three months, the waste amounted to 7,049 sheets, representing 4.35%. After the improvement, from August to October 2024, with an average production order of 159,410 sheets over three months, the waste was reduced to 2,575 sheets, representing 1.62%. Additionally, a work instruction (WI) manual was developed to ensure that all employees followed the standard operating procedures.